Foreign Currency Credit Ratings for Emerging Market Economies - Perrelli, Roberto (IMF Working Papers; Working Paper ;, 2001)
This paper examines how ratings for emerging market economies have been set. Given the high degree of autocorrelation in ratings, we use estimators that yield consistent parameters in the presence of such correlation. The results show that rating changes for emerging market economies have been dominated by variables different from those suggested by the literature. We also conclude that some deterioration in the ratings was warranted during the recent crisis episodes in view of the behavior of economic fundamentals, but that the agencies overreacted for several key countries. We find evidence of a structural break: since the Asian crisis period, ratings have been influenced by reserves in relation to short-term debt.